Introduction: India’s odyssey through International Affairs - de Estrada, K (Oxford University Press, 2017)
The coincidence of Gandhi’s arrest, trial and imprisonment with the first issue of the then Journal of the British Institute of International Affairs, published in early 1922, positions the journal’s birth against the backdrop of the impending twilight of British colonialism in India. International Affairs was, and remains, the flagship publication of Chatham House, itself an institution set up in 1919 ‘to collect, examine and distribute information on imperial and foreign, political, economic and social problems’.